A multi-measure and hybrid iterative procedure for marine ports (re)design. (2017) - Nicoletti, Letizia; Padovano, Antonio
In view of the high terminal construction and maintenance costs, environmental impacts and risk of shipping accidents, public bodies, port authorities, and terminal operators all around the world are looking for new decision support methodologies, especially in the case of large-scale marine ports (re)design projects. The authors propose a multi-measure, hybrid, and iterative procedure, which benefits from the use of real-time simulation to drive the design engineers through a continuous and gradual improvement of the design solution. After having defined multiple performance metrics (margins for safety, pollutant emissions) as well as having designed and implemented a realistic virtual test environment, the design solutions can be generated according to throughput and traffic requirements, and then tested by key nautical experts. Criticalities as well as potential improvements of the design solution are visually reported according to a set of results statistically collected at the end of each testing session.